Індивідуально-профілактичні засоби запобігання злочинам проти життя та здоров'я засуджених до позбавлення волі - Рябих, Н.; Riabykh, N.; Колб, О.; Kolb, О. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено індивідуально-профілактичні заходи запобігання злочинам проти життя та здоров’я засуджених до позбавлення волі. Вивчено зміст індивідуально-профілактичних заходів запобігання злочинам проти життя та здоров’я засуджених до позбавлення волі. Розкрито позиції науковців і практиків щодо проблем індивідуально-профілактичних заходів запобігання злочинів проти життя та здоров'я засуджених, а також внесені певні пропозиції щодо вдосконалення чинного законодавства у цій сфері. The article studies individual preventative measures to prevent crimes against life and health of persons sentenced to imprisonment. The emphasis is laid on the content of individual preventive measures aimed at preventing crimes against life and health of persons sentenced to imprisonment. The authors reveal the positions of scientists and practitioners on the issues of individual preventive measures to prevent crimes against life and health of prisoners and make some suggestions of improving the existing legislation in this area. To prevent crime against life and health of the sentenced to imprisonment the following measures should be applied: 1) to identify individuals whose actions and convictions indicate a real possibility that they can commit such crimes; 2) to conduct a comprehensive analysis of the behavior of these individuals and determine the source of the negative influence on them; 3) to identify opportunities andways of neutralizing sources of negative impact onthe subjects under prevention measures, and explore options for preventing or stopping criminal actions ofthe latter in case the preventive measures appear to beunsuccessful; 4) control over the behavior of thepersons predisposed to commit these crimes, periodic inspection of the results of the preventive measures applied to them.
Individual Preventive Measures to Prevent Crimes Against Life and Health of Persons Sentenced to Imprisonment.
Keywords: індивідуально-профілактичні заходи; злочини проти життя та здоров’я особи; особи схильні до вчинення злочинів; crimes against life and health; the persons predisposed to commit crimes; individual preventive measures